WINDOW FOR SELLING FOREIGN CURRENCY AND DOCUMENTARY CREDITS AND THEIR MUTUAL RELATIONSHIP WITH THE TRADE BALANCE - Salam hashim mohammad; Kamal Kazem Jawad; Hamed Mohsen Jadah (Scholars Digest Publishing, 2024)
The need to reduce the exit of the dollar from the country abroad has become one of the main policies that the Central Bank of Iraq is working to achieve, as the research aimed to study (the reciprocal relationship between the foreign currency sales window and documentary credits and their reciprocal relationship with the trade balance) through the standard causality test (Toda). -Yamamoto) using statistical methods (spss and eveiws10) in order to identify the causal relationship between the study variables and which one is the cause of the other, in addition to using the Barron-Kenny statistical model to study the intermediate relationship between the study variables, and the study concluded that there is a significant effect of foreign currency sales on total imports. The trade balance with the variable: the total documentary credit granted by Iraqi commercial banks, and this is consistent with the logic of the economic theory of the Central Bank of Iraq, which aims to link foreign window sales with the total documentary credit in influencing imports and compensating the shortfall in the gross domestic product of goods and services through imports that It is through documentary credit to buy dollars from the foreign currency selling window. But with a very low impact factor, the study also concluded that both the total documentary credit and window sales of foreign currency are the main cause of trade balance imports, as this was achieved through the significance of the probability (prob), which was less than (5%) and that imports are the main cause. For the window to sell foreign currency, this was achieved through the significance of the probability (prob), which was less than (5%), while the total documentary credit was not the main reason for the window to sell foreign currency, and that both imports, the Iraqi trade balance, and the window’s sales of foreign currency were not the main reason. In increasing or decreasing the total documentary credit for Iraqi commercial banks, that is, it was not the main reason, and this was achieved through the insignificant probability (prob), which achieved a percentage higher than (5%). The study recommended that achieving significance in the effect of foreign currency sales on the total documentary credit. Despite the low values of the documentary credit compared to the volume of the window’s foreign currency sales and very large imports, it shows the success of the Central Bank in this aspect, but it requires many plans and policies in order for the desired goal to be achieved by the Central Bank of Iraq to be achieved. Also, the role played by the Central Bank of Iraq in achieving the causal relationship between the window’s foreign currency sales, imports, and documentary credit is simple due to the lack of efficient private and governmental commercial banks that help in achieving this role, as commercial banks suffer from a weak number of correspondent commercial banks abroad. The almost total reliance on the Iraqi Trade Bank, and even more than that, there are no plans showing that these commercial banks are destined to reform their affairs and achieve higher levels.
Keywords: Foreign currency sales window, documentary credits, trade balance.